Bioactive natural products : detection, isolation, and structural determination - Colegate, Steven M., ....-; Molyneux, Russell J., ....- (Boca Raton : CRC, 2008)
Following the successful format of the first edition, Bioactive Natural Products: Detection, Isolation, and Structural Determination, Second Edition presents applications of the most recent techniques for the detection, isolation, and structural determination of bioactive natural products. This second edition features new case studies and illustrations that demonstrate practical applications of techniques covered in the book. Complementing the first edition, most of the contributors are new. The text includes updates on bioactive chemical extraction, and NMR-based structure determination, and new contributions on liquid chromatography linked with mass spectrometry and NMR spectroscopy, dereplication approaches, assessment of source material for bioactive natural products and novel bioassay development.